Aspectos executivos e a qualidade de estruturas em concreto armado : estudo de caso - Takata, Leandro Teixeira (Universidade Federal de São Carlos, 2009)
The execution of reinforced concrete structures is a construction stage that has significant importance in the overall context of a work and involves materials, suppliers, work fronts in the workplace and a large number of professionals. In this stage many problems may occur: inadequate use of materials, misinterpretation of the project, incorrect use of equipments, action of weather and other inconveniences. Carelessness at this stage can lead to major schedule delays and extra costs, as this will require new tasks, materials and equipment not predicted (a new set of forms can be used, but the material and labor for the service may not be available). Surveillance and attention are needed for a good final product which, however, is not always achieved. That is where the pathology of structures acts, aiming to correct and prevent failures in all constructive stages. Otherwise, problems may appear in the global chain of the work, leading to the need to restructure the process of execution of the building. Therefore, several authors propose standard, and even alternative, construction methods, companies provide manuals of performance and quality control of materials and the codes propose minimum requirements for safety, durability and quality of buildings. To study and improve the execution phase means, therefore, avoiding delays and additional costs, as well as ensuring that the building will have quality and durability. This paper analyzes the execution phase of a given multiple floor building, pointing out mistakes and their possible influences on the quality of the building during its service life.
Keywords: Concreto armado; Estruturas de concreto armado; Execução de estruturas; Patologia das estruturas; Reinforced concrete; Pathology of structures; Structure execution; ENGENHARIAS::ENGENHARIA CIVIL::CONSTRUCAO CIVIL